ERP Driven Digital Transformation in the Context of Supply Chain Management - Gajwel, Sreekanth (Digital Repository of Theses, 2025)
ERP-driven digital transformation has emerged as a pivotal factor in revolutionizing supply chain management (SCM), particularly in industries seeking to enhance operational efficiency, agility, and resilience. This study inspects the impression of ERP systems on digital transformation within the supply chain context, focusing on how cloud-based and on-premise ERP solutions contribute to improved supply chain performance and adaptability amidst disruptions and uncertainties. The research examines the integration of employee competency and training as a critical intermediary variable, facilitating the effective utilization of digital transformation technologies and their subsequent effect on organizational outcomes. By employing Partial Least Squares Structural Equation Modeling (PLS-SEM) as the primary methodical tool, the study evaluates both the measurement and structural models to test the proposed hypotheses and validate the conceptual framework. The discoveries highlight the noteworthy role of ERP systems in driving supply chain innovation and efficiency. Cloud-based ERP systems demonstrate a robust positive impact on digital transformation technologies, highlighting their scalability, accessibility, and potential to enhance decision-making processes. On-premise ERP systems also contribute significantly, albeit to a lesser extent, emphasizing their reliability in specific operational contexts. Employee competency and training emerged as a vital factor, mediating the association amid ERP adoption and digital transformation consequences. The results designate that well-trained employees are well fortified to influence ERP functionalities, thereby facilitating the unified addition of digital transformation technologies into supply chain procedures. In terms of outcomes, digital transformation technologies were found to significantly enhance supply chain performance, as evidenced by improved operational metrics, reduced lead times, and better resource allocation. Furthermore, these technologies contribute to increased supply chain agility and resilience, enabling organizations to adapt to market disruptions, unforeseen challenges, and evolving customer demands. The study’s structural model demonstrated high predictive accuracy, with strong path coefficients and satisfactory R-squared values for the dependent variables, affirming the robustness of the planned framework. This research provides several practical implications for industry stakeholders. Organizations are encouraged to prioritize investments in cloud-based ERP systems and employee training programs to maximize the benefits of digital transformation. Additionally, businesses should adopt a holistic approach that integrates ERP technologies with emerging tools such as Blockchain, IoT, and Artificial Intelligence to further augment supply chain discernibility and efficiency. Policymakers and industry leaders are urged to create enabling environments, including inducements and regulatory outlines, to promote the widespread acceptance of ERP systems. Forthcoming research instructions include longitudinal studies to measure the longstanding effects of ERP-driven digital transformation and comparative analyses across diverse sectors and geographical regions. Exploring the integration of ERP systems with sustainability initiatives, such as carbon footprint management and waste reduction, could deliver valuable visions into the environmental implications of digital transformation in supply chains. Moreover, investigating the unique challenges and opportunities confronted by small and medium-sized enterprises (SMEs) in accepting ERP systems would enrich the current understanding of digital transformation dynamics across organizational scales. In inference, this study establishes a all-inclusive framework for understanding the interplay between ERP systems, employee competency, and digital transformation technologies in the context of supply chain management. By bridging theoretical insights with empirical evidence, it proposals actionable references for organizations aiming to navigate the complexities of digital transformation and attain sustainable competitive advantages.